การศึกษาสมรรถนะการทำความเย็นของระบบพัดลมไอน้ำพลังงานรังสีอาทิตย์: Performance Study of Solar Evaporative Cooling Fogging Fan System - Mansiri, Kongrit; Ketjoy, Nipon (Asian Health, Science and Technology Reports, 2010)
This research presents the solution of reducing outdoor temperature by solar evaporative fogging Fan. The solar evaporative fogging fan was installed in the Energy Park of School of Renewable Energy Technology (SERT), Narasuan University. The components of system consisted of 4 parts: 24 inch (190 W) fogging fan, 465 W steam high pressure pump, 6 kWh (12 V×120 Ah×4 units) battery and 1,000 W inverter. After the system was installed, it was evaluated in term of technique. The results were found that the prototype of solar fogging fan worked well with electricity form solar cell system, and the temperature of conditioning area was reduced 1.17 o C by solar fogging fan compare to non - conditioning area and average humidity of conditioning area was higher than non – conditioning area 5.56 %. The efficiency of evaporative cooling was 19.14 %, and the average evaporative cooling rate was 8,890 Btu/hr. The ratio of electrical energy per cooling energy which was used to evaporate water was 5.03 kWhcooling /kWhelectric